Trehalose-loaded LNPs enhance mRNA stability and bridge in vitro in vivo efficacy gap - Xu-Han Liu; Hui-Ping Song; Ling-Ling Tao; Zhe Zhai; Jin-Xing Huang; Yong-Xian Cheng (npj Vaccines)
Abstract Lyophilization enhances mRNA vaccine stability, but conventional approaches using external trehalose for lipid nanoparticle (LNP) colloidal stability neglect mRNA chemical degradation and are compromised in vivo efficacy. Here, we report a dual-function trehalose strategy integrating its external and internal roles within LNP. This strategy enables trehalose to externally form a vitrified matrix that preserves LNP colloidal integrity, while internally stabilizing mRNA through hydrogen bonding, markedly reducing chemical degradation during storage compared to LNP relying solely on externally added trehalose. Crucially, co-loaded trehalose is co-delivered into cells, bridging the in vitro-in vivo gap by mitigating oxidative stress through reduced reactive oxygen species (ROS) and malondialdehyde (MDA) alongside elevated glutathione (GSH) and superoxide dismutase (SOD). This is corroborated by downregulated cytoplasmic and nuclear nuclear factor erythroid 2-related factor 2 (Nrf2) expression. Our strategy provides a simple, universally adaptable, and scalable method to enhance mRNA-LNP formulations stability without exogenous components or complex lyophilization steps.